Original paperDual-source computed tomography angiography in patients after bypass grafting – comparison with invasive coronary angiography - Kępka, Cezary; Opolski, Maksymilian P.; Kruk, Mariusz; Pręgowski, Jerzy; Michałowska, Ilona; Demkow, Marcin; Witkowski, Adam; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
Background: Assessment of bypass grafts by invasive coronary angiography (ICA) is bothersome and often requires extra procedure time, contrast load, and radiation exposure. Aim: To evaluate the ability of dual-source computed tomography angiography (CTA) to detect significant graft disease in symptomatic patients after coronary artery bypass grafting (CABG). Methods: Thirty (26 men, mean age 66 ± 9 years) consecutive post-CABG patients from the prospective ANIN Computed Tomography Angiography Registry who underwent both dual-source CTA and ICA for suspected graft disease were included in the analysis. Coronary artery bypass grafts, anastomotic sites, and distal runoffs with a diameter of ≥ 1.5 mm were evaluated for the presence of significant stenoses (≥ 50% diameter reduction). Invasive coronary angiography served as a reference standard, and was performed within ≤ 30 days of dual-source CTA. Results: A total of 58 bypass grafts with 56 anastomotic sites, and 54 distal runoffs were evaluable both in dual-source CTA and ICA. Sensitivity, specificity, and positive and negative predictive values of dual-source CTA for the detection of significant lesions in bypass grafts were 100%, 92%, 86%, and 100%, respectively. In anastomotic sites, dual-source CTA detected significant stenosis with a sensitivity and specificity of 100% and 96%, respectively. If analysis was restricted to distal runoff segments, sensitivity and specificity were 50% and 98%, respectively. On a per-patient basis, all patients with at least one significant graft stenosis on ICA were correctly classified using dual-source CTA. Conclusions: Dual-source CTA permits the reliable assessment of bypass graft disease with high diagnostic accuracy and can be used in clinical routine as a noninvasive test to rule out suspected graft dysfunction in symptomatic post-CABG patients.